Current Issues in Terminology and Classification of Hereditary Disorders at Endocrine Cancer - S. B. Pinsky; V. A. Beloborodov; V. V. Dvornichenko; Yu. K. Batoroev; V. A. Vorobev (Acta Biomedica Scientifica)
Significant interest in the problem of genetic oncological diseases is due to an increase in the frequency of their detection, existing difficulties of early recognition, disagreements in the clinical and morphological criteria for diagnosis and evaluation of prognostic factors, the absence of generally accepted standards of treatment and objective assessment of their results.The introduction of new diagnostic technologies into clinical practice (molecular genetic studies, the ability to determine a wide range of hormones and peptides, immunohistochemical determination of general and specific markers, modern methods of topical diagnostics, etc.) allowed us to identify a specific genetic substrate of various types of endocrine organ tumors, previously unknown nosological forms, improve the ability to predict the disease on the preclinical level, to assess their place and importance in the structure of general oncopathology.The issues of terminology, classification, criteria for the degree of malignancy and prognostic factors of hereditary endocrine diseases are particularly relevant. The article presents and analyzes the modern classification and terminological definitions of this group of diseases. The problem of hereditary endocrine tumor diseases and syndromes associated with neuroendocrine tumors (NETs) and multiple endocrine neoplasia syndromes (MEN-syndromes) has been described. In conclusion, the situation with the study of this problem in the Russian Federation is analyzed.